A method for producing potassium salt co-production of magnesium saponite by calcination-hydrothermal composite method

CN122977407APending Publication Date: 2026-10-27QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611259514.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]现有的钾长石综合利用工艺路线主要包括:整体制备钾硅多元肥、分解后逐级提取、尾渣制备复合材料等,上述方法存在或者工艺路线复杂,或者产品品质低,或者产品附加值低等问题

Benefits of technology

(1)相比钙盐和钠盐煅烧工艺所得的钾钙硅肥,本发明所得产品为硫酸钾镁肥和镁皂石,获得水溶性钾肥的同时,联产稀缺人工矿物材料镁皂石;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a method for producing potassium salt and co-producing magnesium soapstone by using a calcination-hydrothermal composite method. The method comprises the following steps: crushing a mineral containing potassium feldspar, mixing the crushed mineral with a calcination aid, and then performing calcination, acid leaching and solid-liquid separation treatment to obtain an aluminum silicate gel solid and a sulfate mixed solution; performing neutralization, de-aluminum, evaporation, concentration and crystallization on the sulfate mixed solution to obtain hydrated potassium magnesium sulfate, an aluminum salt precipitate and a crystallization tail liquid; and mixing the aluminum salt precipitate, the crystallization tail liquid and the aluminum silicate gel solid, and adjusting the pH value to 8-11, and then performing hydrothermal reaction to obtain the magnesium soapstone. The application provides a green potassium extraction process for potassium feldspar without tailings and with full circulation of a material liquid, produces potassium magnesium sulfate fertilizer while co-producing magnesium soapstone, realizes comprehensive utilization of potassium feldspar resources, reduces the cost of potassium extraction, and improves the economic feasibility of the comprehensive utilization process of the potassium feldspar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of comprehensive utilization technology of potassium feldspar minerals, specifically relating to a method for producing potassium salts and co-producing magnesium saponite using a calcination-hydrothermal composite method. Background Technology

[0003] my country has abundant potassium-rich rock resources, such as potassium feldspar, with reserves far exceeding those of soluble potassium salts. These rocks are characterized by their variety and wide distribution, and can be found in volcanic, sedimentary, and metamorphic rocks. Potassium-containing rocks with a potassium oxide content greater than 8% are widely distributed, providing favorable conditions for the development of potash fertilizers.

[0004] Developing new processes for producing potash fertilizer from potassium feldspar and other potassium-rich rocks as alternative resources to soluble potassium ore can not only make up for the shortage of soluble potassium ore resources, but also achieve the sustainable development of the potash fertilizer industry and ensure the long-term effective supply of potash fertilizer. This has broad application prospects and important practical significance.

[0005] Currently, for every ton of potash fertilizer produced from potassium feldspar, 11-18 tons of waste residue are generated as a byproduct. The high cost of waste residue treatment significantly increases the production cost of potash fertilizer, severely hindering the industrial application of potash fertilizer production technology using potassium feldspar. With my country's increasing emphasis on environmental protection, the comprehensive utilization of potassium feldspar resources must be achieved during the potassium extraction process. Utilizing potassium feldspar to simultaneously produce high-value-added products is the trend in technology development.

[0006] Magnesium saponite is a rare mineral found globally, but it has a high impurity content and is difficult to purify.

[0007] Synthetic magnesium saponite is a 2:1 type trioctahedral layered silicate material with thermal stability and functional customization capabilities far exceeding those of natural clay minerals. It is an important inorganic nanomaterial for high-end industrial and daily chemical fields. It has wide applications in high-temperature drilling mud, thickeners, catalyst carriers, and pollutant adsorption.

[0008] Existing comprehensive utilization processes for potassium feldspar mainly include: overall preparation of potassium-silicon multi-element fertilizer, stepwise extraction after decomposition, and preparation of composite materials from tailings. These methods have problems such as complex process routes, low product quality, or low added value.

[0009] Existing potassium-feldspar extraction processes use the calcination of calcium and sodium salts to obtain potassium-silicon-calcium fertilizers, resulting in low K2O content, a small service radius, and difficulty in replacing water-soluble potassium fertilizers. Hydrothermal production of water-soluble potassium fertilizers generates large amounts of calcium and sodium salt waste. Direct utilization of this waste to produce composite materials results in low product value and limited market absorption. Separating and extracting elements from the waste individually presents challenges in quality control, high purification costs, and weak market competitiveness for related products. More importantly, the harmful elements generated during simultaneous activation are not effectively solidified, accumulating in citrate-soluble potassium fertilizers and the waste liquid and residue after potassium extraction, posing environmental risks and hazards. Summary of the Invention

[0010] The main objective of this invention is to provide a method for producing potassium salts and magnesium saponite using a calcination-hydrothermal composite method, thereby overcoming the shortcomings of the prior art.

[0011] To achieve the aforementioned objectives, the technical solution adopted by this invention includes: This invention provides a method for producing potassium salts and co-producing magnesium saponite using a calcination-hydrothermal composite method, comprising: Potassium-containing feldspar minerals are crushed, then mixed with calcination aids and subjected to calcination, acid leaching, and solid-liquid separation to obtain aluminosilicate gel solid and sulfate mixed solution; wherein, the calcination aids include magnesium compounds or a mixture of magnesium compounds and magnesium substitutes. The sulfate mixture solution was neutralized, dealuminized, evaporated, concentrated and crystallized to obtain hydrated potassium magnesium sulfate, aluminum salt precipitate and crystallization tail liquid; Furthermore, the aluminum salt precipitate, crystallization tail liquid, and aluminosilicate gel solid are mixed and the pH value is adjusted to 8-11, followed by a hydrothermal reaction to obtain magnesium soapstone.

[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Compared with the potassium-calcium-silicon fertilizer obtained by the calcium salt and sodium salt calcination process, the product obtained by the present invention is potassium magnesium sulfate fertilizer and magnesium saponite, which obtains water-soluble potassium fertilizer and co-produces the scarce artificial mineral material magnesium saponite. (2) Compared with the hydrothermal method for producing water-soluble potassium fertilizer, the present invention does not produce waste residue, and the great adjustability of the composition and function of magnesium saponite provides convenience for the full utilization of by-products. (3) Compared with magnesium salt thermal activation of potassium feldspar, high-temperature calcination greatly improves the effective reaction ratio between magnesium salt and potassium feldspar, eliminating the need for excessive magnesium salt and facilitating the recycling of materials. (4) Compared with the existing potassium feldspar activation process, the present invention has a strong adaptability to potassium feldspar raw materials. Even if there are a certain amount of harmful elements in the raw materials, they can be effectively solidified in the magnesium saponite synthesis process, which greatly reduces the environmental risks and hidden dangers in the potassium extraction process of potassium feldspar. (5) In terms of the economics of potassium extraction from potassium feldspar, traditional methods often require the K2O content in potassium feldspar to be no less than 10 wt.%, which places high demands on the beneficiation of potassium feldspar ore. Domestic commercial potassium feldspar is mostly associated with sodium feldspar, and the K2O content in the product is mostly between 6-8 wt.%, which is difficult to meet the requirements of traditional methods. In the potassium extraction process of this invention, magnesium saponite is produced in situ. Magnesium saponite can not only realize the in-situ utilization of silicon and aluminum elements in sodium feldspar, but also realize the insertion of sodium ions in the interlayer. Therefore, the requirement for K2O content in potassium feldspar can be reduced to about 8 wt.%, which expands the application range and market value of slightly lower grade potassium feldspar. Detailed Implementation

[0013] In view of the deficiencies of the prior art, the applicant of this case, through long-term research and extensive practice, has been able to propose the technical solution of this invention. This invention starts from the overall comprehensive utilization of potassium feldspar, uses magnesium-based alkaline compounds as roasting aids to activate potassium feldspar, uses sulfuric acid leaching solution to produce potassium magnesium sulfate fertilizer, utilizes the layering ability of magnesium ions on silicate compounds, and uses by-products such as aluminosilicate gel, magnesium sulfate, and crystallization tailings to synthesize magnesium soapstone. While producing potassium fertilizer, it also produces scarce mineral materials, and simultaneously solidifies harmful elements activated during calcination and acid leaching, achieving zero tailings and full recycling of the liquid, thereby improving the market competitiveness of the product and the greenness of the process.

[0014] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0015] Specifically, as one aspect of the technical solution of this invention, a method for producing potassium salts and co-producing magnesium saponite using a calcination-hydrothermal composite method includes: Potassium-containing feldspar minerals are crushed, then mixed with calcination aids and subjected to calcination, acid leaching, and solid-liquid separation to obtain aluminosilicate gel solid and sulfate mixed solution; wherein, the calcination aids include magnesium compounds or a mixture of magnesium compounds and magnesium substitutes. The sulfate mixture solution was neutralized, dealuminized, evaporated, concentrated and crystallized to obtain hydrated potassium magnesium sulfate, aluminum salt precipitate and crystallization tail liquid; Furthermore, the aluminum salt precipitate, crystallization tail liquid, and aluminosilicate gel solid are mixed and the pH value is adjusted to 8-11, followed by a hydrothermal reaction to obtain magnesium soapstone.

[0016] In some preferred embodiments, the potassium feldspar in the potassium-containing mineral includes any one or more combinations of microcline, orthoclase, sorbite, and sanidine, and is not limited thereto.

[0017] In some preferred embodiments, the potassium feldspar mineral is mainly potassium feldspar, while containing small amounts of impurities and associated minerals such as quartz, albite, and dolomite.

[0018] In some preferred embodiments, potassium feldspar-containing minerals are pulverized to a particle size of 50 to 400 mesh, and the pulverized product is mixed with a calcining aid by stirring, mechanical ball milling, or extrusion mixing.

[0019] In some preferred embodiments, the magnesium compound includes any one or more combinations of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, hydrated magnesium silicate, hydrated magnesium carbonate, basic magnesium carbonate, magnesite, hydromagnesite, and hydrocrystalline magnesite, and is not limited thereto.

[0020] In some preferred embodiments, the magnesium substitute compound includes any one or more combinations of sodium compounds, lithium compounds, and zinc compounds, but is not limited thereto.

[0021] Furthermore, the magnesium substitute compound includes, but is not limited to, any one or more combinations of oxides, carbonates, hydroxides, and silicates of sodium, lithium, or zinc.

[0022] In some preferred embodiments, the molar ratio of the metal element in the magnesium substitute compound to the magnesium element in the magnesium compound in the mixture formed by the magnesium compound and the magnesium substitute compound is ≤1.

[0023] In some preferred embodiments, the potassium feldspar-containing minerals and roasting aids used have a MgO / SiO2 molar ratio of 4 to 8, calculated as MgO / SiO2.

[0024] In some preferred embodiments, the method includes: crushing potassium feldspar minerals, mixing them with a roasting aid and calcining them at 850-1300°C for 1-5 hours, cooling them to 200-300°C, mixing the obtained product with a sulfuric acid solution to form a solid-liquid system at 50-100°C and performing thorough leaching, and finally separating the solid and liquid to obtain an aluminosilicate gel solid and a sulfate mixed solution.

[0025] Furthermore, the concentration of the sulfuric acid solution is 2~9 mol / L, and the concentration of the sulfuric acid solution in the solid-liquid system after complete leaching is 0.01~0.05 mol / L.

[0026] Furthermore, the initial concentration of the sulfuric acid solution is between 2 and 9 mol / L, and the final concentration is between 0.01 and 0.05 mol / L.

[0027] Furthermore, the leaching time is 1 to 10 hours.

[0028] Furthermore, the cations in the sulfate mixed solution include magnesium ions, potassium ions, sodium ions, and aluminum ions.

[0029] Furthermore, the sulfate mixed solution mainly contains magnesium, potassium, sodium and a small amount of aluminum ions.

[0030] In some preferred embodiments, the method includes: adding magnesium oxide and / or magnesium hydroxide to the sulfate mixture for neutralization treatment, and adjusting the pH value to 6.0-7.5.

[0031] In some preferred embodiments, the dealuminization is performed by adding polyaluminum chloride to the product obtained from neutralization.

[0032] In some preferred embodiments, the crystallization temperature is -10°C to 35°C.

[0033] In some preferred embodiments, the products obtained after crystallization include hydrated magnesium sulfate, magnesium sulfate heptahydrate, sodium sulfate, and anhydrous sodium sulfate.

[0034] In some preferred embodiments, the crystallization sequence of the crystallization products is determined by the proportion and concentration of the components in the solution and the ambient temperature. Possible products include: hydrated potassium magnesium sulfate, magnesium sulfate heptahydrate, sodium sulfate, anhydrous sodium sulfate, etc., and the main component of the crystallization tail liquid is magnesium sulfate, etc.

[0035] In some preferred embodiments, the crystallization tail liquid after crystallization includes a magnesium sulfate solution.

[0036] In some preferred embodiments, the method further includes: washing and dehydrating the hydrated potassium magnesium sulfate to obtain potassium magnesium sulfate fertilizer.

[0037] In some preferred embodiments, the aluminum salt precipitate, crystallization tail liquid, and aluminosilicate gel solid used have a molar ratio of SiO2 / Al2O3 of 6 to 24 and a molar ratio of MgO / Al2O3 of 4 to 10, based on SiO2 / Al2O3 and MgO / Al2O3, respectively.

[0038] In some preferred embodiments, the aluminum salt precipitate, crystallization tail liquid, and aluminosilicate gel solid are mixed and the pH value is adjusted using a pH adjusting agent, which includes any one or more combinations of magnesium hydroxide, magnesium oxide, sodium carbonate, and sodium hydroxide.

[0039] In some preferred embodiments, the hydrothermal reaction is carried out at a temperature of 80-300°C for a duration of 2 hours to 12 days.

[0040] In some preferred embodiments, the method for producing potassium salts and co-producing magnesium saponite using a calcination-hydrothermal composite method includes: Potassium feldspar minerals are crushed to a certain particle size. Magnesium compounds and potassium feldspar minerals are thoroughly and uniformly mixed in a certain proportion. The mixture is then calcined at high temperature and cooled to a certain temperature. The resulting product is then immersed in sulfuric acid solution. After thorough leaching, solid-liquid separation is performed to obtain aluminosilicate gel solid and sulfate mixed solution. The aluminosilicate gel solid is washed, and the acidic washing liquid is recovered and reused in the acid leaching section of the calcined product. The sulfate mixed solution is neutralized, dealuminized, evaporated, concentrated, and crystallized to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer), hydrated magnesium sulfate (if magnesium compounds are added in excess, hydrated magnesium sulfate will crystallize before potassium magnesium alum precipitates), and magnesium-containing crystallization tail liquid. Hydrated magnesium sulfate (if any), magnesium-containing crystallization tail liquid, aluminosilicate gel, and dealuminized precipitate are mixed in a certain proportion, the pH of the solution is adjusted, and magnesium soapstone is hydrothermally synthesized. The synthesized tail liquid is returned to the sulfuric acid leaching section.

[0041] The process of this invention was designed from the outset to take into account the activation and extraction of potassium ions, the comprehensive utilization of silicon and aluminum, and the solidification of harmful elements. By introducing magnesium compounds that can form potassium-magnesium compound fertilizer with potassium salts and layered silicate materials with silicon and aluminum, magnesium soapstone is synthesized while potassium ions are activated and potassium magnesium sulfate fertilizer is produced, and the harmful elements activated during the potassium extraction process are solidified simultaneously.

[0042] The purpose of this invention is to develop a green potassium extraction process for potassium feldspar that is free of tailings and allows for the complete recycling of the feed liquid, producing potassium magnesium sulfate fertilizer while simultaneously generating magnesium saponite as a byproduct, thereby achieving comprehensive utilization of potassium feldspar resources, reducing potassium extraction costs, and improving the economic feasibility of potassium feldspar comprehensive utilization processes.

[0043] The technical solution of the present invention will be further described in detail below with reference to several preferred embodiments. These embodiments are implemented on the premise of the technical solution of the invention, and provide detailed implementation methods and specific operation processes. However, the protection scope of the present invention is not limited to the following embodiments.

[0044] Unless otherwise specified, the experimental materials used in the examples below can be purchased from conventional biochemical reagent companies.

[0045] Example 1 Pure-phase potassium feldspar ore, with approximately 15% K₂O by weight, was pulverized to 200 mesh and mixed with magnesium oxide powder. The MgO / SiO₂ molar ratio in the powder mixture was 4. The mixture was calcined at 1000℃ for 2 hours. After calcination, the mixture was cooled to 300℃ and mixed with a 6 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 80℃ and leached with stirring for 3 hours, ending with a sulfuric acid concentration of approximately 0.02 mol / L. Solid-liquid separation yielded amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contained magnesium, potassium, and trace aluminum ions. The pH of the solution was neutralized to approximately 6.0 with magnesium oxide, and polyaluminum chloride was added to remove trace aluminum ions. Solid-liquid separation was then performed, and the aluminum salt precipitate was washed and reused. The washing liquid was returned to the acid leaching section. After dealuminization, the solution is evaporated and concentrated, then crystallized at 20°C to precipitate hydrated potassium magnesium sulfate. Before reaching the crystallization concentration of the chelate salt, solid-liquid separation is performed to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer) and magnesium sulfate solution. The magnesium sulfate solution, aluminosilicate gel, and dealuminized precipitate are mixed, sodium carbonate is added, the pH is adjusted to 10, the silica-alumina ratio is 6, and the magnesium-alumina ratio is 10. The mixture is reacted at 300°C for 2 hours, and then the solid and liquid phases are separated. The solid phase is washed to obtain magnesium soapstone, and the liquid phase is returned to the magnesium soapstone synthesis batching section.

[0046] Comparative Example 1 The method is the same as in Example 1, except that the molar ratio of MgO / SiO2 in the powder mixture is 2.

[0047] Pure-phase potassium feldspar ore, with approximately 15% K₂O by weight, was pulverized to 200 mesh and mixed with magnesium oxide powder. The MgO / SiO₂ molar ratio in the powder mixture was 2. The mixture was calcined at 1000℃ for 2 hours. After calcination, the mixture was cooled to 300℃ and mixed with a 6 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 80℃ and leached with stirring for 3 hours, ending with a sulfuric acid concentration of approximately 0.02 mol / L. Solid-liquid separation yielded undecomposed potassium feldspar, amorphous aluminosilicate gel solids, and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contained magnesium, potassium, and trace aluminum ions. The pH of the solution was neutralized to approximately 6.0 with magnesium oxide, and polyaluminum chloride was added to remove trace aluminum ions. Solid-liquid separation was then performed, and the aluminum salt precipitate was washed and reused. The washing liquid was returned to the acid leaching section. After dealuminization, the solution is evaporated and concentrated, then crystallized at 20°C to precipitate hydrated potassium magnesium sulfate. Before reaching the crystallization concentration of the chelate salt, solid-liquid separation is performed to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer) and magnesium sulfate solution. The magnesium sulfate solution, aluminosilicate gel, and dealuminized precipitate are mixed, sodium carbonate is added, the pH is adjusted to 10, the silica-alumina ratio is 6, and the magnesium-alumina ratio is 10. The mixture is reacted at 300°C for 2 hours, and then the solid and liquid phases are separated. The solid phase is washed to obtain magnesium soapstone, and the liquid phase is returned to the magnesium soapstone synthesis batching section.

[0048] Comparative Example 2 The method is the same as in Example 1, except that the molar ratio of MgO / SiO2 in the powder mixture is 10.

[0049] Pure-phase potassium feldspar ore, with approximately 15% K₂O by weight, was pulverized to 200 mesh and mixed with magnesium oxide powder. The MgO / SiO₂ molar ratio in the powder mixture was 10. The mixture was calcined at 1000℃ for 2 hours. After calcination, the mixture was cooled to 300℃ and mixed with a 6 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 80℃ and leached with stirring for 3 hours. The sulfuric acid concentration at the end of the leaching process was approximately 0.02 mol / L. The addition of excess magnesium oxide increased the acid consumption in the subsequent neutralization process. Solid-liquid separation yielded an amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contains magnesium, potassium, and trace aluminum ions. The pH of the solution is neutralized to approximately 6.0 with magnesium oxide. Polyaluminum chloride is added to remove trace aluminum ions. Solid-liquid separation is performed, and the aluminum salt precipitate is washed and reserved. The washing liquid is returned to the acid leaching section. The dealuminized solution is evaporated, concentrated, and crystallized at 20°C to precipitate hydrated magnesium potassium sulfate. Before reaching the crystallization concentration of the chelate, solid-liquid separation is performed to obtain hydrated magnesium sulfate, hydrated magnesium potassium sulfate (washed and dehydrated to obtain magnesium potassium sulfate fertilizer), and crystallization tail liquid. The addition of excessive magnesium oxide leads to an excessively high magnesium content in the solution system, necessitating an additional crystallization removal stage for hydrated magnesium sulfate. Hydrated magnesium sulfate, aluminosilicate gel, dealuminized precipitate, and crystallization tail liquid are mixed, sodium carbonate is added, and the pH is adjusted to 10. The silica-to-aluminum ratio is 6, and the magnesium-to-aluminum ratio is 10. The mixture is reacted at 300°C for 2 hours, followed by solid-liquid separation. The solid phase is washed to obtain magnesium soapstone, and the liquid phase is returned to the magnesium soapstone synthesis batching section.

[0050] Comparative Example 3 The method is the same as in Example 1, except that the silicon-aluminum ratio is 4 and the magnesium-aluminum ratio is 2 before the hydrothermal reaction.

[0051] Pure-phase potassium feldspar ore, with approximately 15% K₂O by weight, was pulverized to 200 mesh and mixed with magnesium oxide powder. The MgO / SiO₂ molar ratio in the powder mixture was 4. The mixture was calcined at 1000℃ for 2 hours. After calcination, the mixture was cooled to 300℃ and mixed with a 6 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 80℃ and leached with stirring for 3 hours, ending with a sulfuric acid concentration of approximately 0.02 mol / L. Solid-liquid separation yielded amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contained magnesium, potassium, and trace aluminum ions. The pH of the solution was neutralized to approximately 6.0 with magnesium oxide, and polyaluminum chloride was added to remove trace aluminum ions. Solid-liquid separation was then performed, and the aluminum salt precipitate was washed and reused. The washing liquid was returned to the acid leaching section. After dealumination, the solution was evaporated and concentrated, and crystallized at 20°C to precipitate hydrated potassium magnesium sulfate. Before reaching the crystallization concentration of the chelate salt, solid-liquid separation was performed to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer) and magnesium sulfate solution. The magnesium sulfate solution, aluminosilicate gel, and dealumination precipitate were mixed, sodium carbonate was added, and the pH was adjusted to 10. The silica-alumina ratio was 4, and the magnesium-alumina ratio was 2. The mixture was reacted at 300°C for 2 hours, and solid-liquid separation was performed. The solid phase was washed to obtain a mixture of magnesium aluminum hydrotalcite and magnesium soapstone.

[0052] Comparative Example 4 The method is the same as in Example 1, except that the silicon-to-aluminum ratio is 30 and the magnesium-to-aluminum ratio is 15 before the hydrothermal reaction.

[0053] Pure-phase potassium feldspar ore, with approximately 15% K₂O by weight, was pulverized to 200 mesh and mixed with magnesium oxide powder. The MgO / SiO₂ molar ratio in the powder mixture was 4. The mixture was calcined at 1000℃ for 2 hours. After calcination, the mixture was cooled to 300℃ and mixed with a 6 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 80℃ and leached with stirring for 3 hours, ending with a sulfuric acid concentration of approximately 0.02 mol / L. Solid-liquid separation yielded amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contained magnesium, potassium, and trace aluminum ions. The pH of the solution was neutralized to approximately 6.0 with magnesium oxide, and polyaluminum chloride was added to remove trace aluminum ions. Solid-liquid separation was then performed, and the aluminum salt precipitate was washed and reused. The washing liquid was returned to the acid leaching section. After dealumination, the solution was evaporated and concentrated, then crystallized at 20°C to precipitate hydrated potassium magnesium sulfate. Before reaching the crystallization concentration of chelate salt, solid-liquid separation was performed to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer) and magnesium sulfate solution. The magnesium sulfate solution, aluminosilicate gel, and dealuminated precipitate were mixed, sodium carbonate was added, and the pH was adjusted to 10. The silica-alumina ratio was 30, and the magnesium-alumina ratio was 15. The mixture was reacted at 300°C for 2 hours, and then solid-liquid separation was performed. The solid phase was washed to obtain a mixture of zeolite, hydrated silica, and magnesium saponite.

[0054] Comparative Example 5 The method is the same as in Example 1, except that the pH is adjusted to 7 before the hydrothermal reaction.

[0055] Pure-phase potassium feldspar ore, with approximately 15% K₂O by weight, was pulverized to 200 mesh and mixed with magnesium oxide powder. The MgO / SiO₂ molar ratio in the powder mixture was 4. The mixture was calcined at 1000℃ for 2 hours. After calcination, the mixture was cooled to 300℃ and mixed with a 6 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 80℃ and leached with stirring for 3 hours, ending with a sulfuric acid concentration of approximately 0.02 mol / L. Solid-liquid separation yielded amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contained magnesium, potassium, and trace aluminum ions. The pH of the solution was neutralized to approximately 6.0 with magnesium oxide, and polyaluminum chloride was added to remove trace aluminum ions. Solid-liquid separation was then performed, and the aluminum salt precipitate was washed and reused. The washing liquid was returned to the acid leaching section. After dealuminization, the solution was evaporated and concentrated, then crystallized at 20°C to precipitate hydrated potassium magnesium sulfate. Before reaching the crystallization concentration of chelate salt, solid-liquid separation was performed to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer) and magnesium sulfate solution. The magnesium sulfate solution, aluminosilicate gel, and dealuminized precipitate were mixed, sodium carbonate was added, and the pH was adjusted to 10. The silica-alumina ratio was 6, and the magnesium-alumina ratio was 7. The mixture was reacted at 300°C for 2 hours, and then solid-liquid separation was performed. The solid phase was washed to obtain a mixture of magnesium aluminum silicate gel and magnesium soapstone.

[0056] Comparative Example 6 The method is the same as in Example 1, except that the pH is adjusted to 12 before the hydrothermal reaction.

[0057] Pure-phase potassium feldspar ore, with approximately 15% K₂O by weight, was pulverized to 200 mesh and mixed with magnesium oxide powder. The MgO / SiO₂ molar ratio in the powder mixture was 4. The mixture was calcined at 1000℃ for 2 hours. After calcination, the mixture was cooled to 300℃ and mixed with a 6 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 80℃ and leached with stirring for 3 hours, ending with a sulfuric acid concentration of approximately 0.02 mol / L. Solid-liquid separation yielded amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contained magnesium, potassium, and trace aluminum ions. The pH of the solution was neutralized to approximately 6.0 with magnesium oxide, and polyaluminum chloride was added to remove trace aluminum ions. Solid-liquid separation was then performed, and the aluminum salt precipitate was washed and reused. The washing liquid was returned to the acid leaching section. After dealumination, the solution was evaporated and concentrated, and crystallized at 20°C to precipitate hydrated potassium magnesium sulfate. Before reaching the crystallization concentration of the chelate salt, solid-liquid separation was performed to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer) and magnesium sulfate solution. The magnesium sulfate solution, aluminosilicate gel, and dealuminated precipitate were mixed, sodium carbonate was added, and the pH was adjusted to 12. The silica-alumina ratio was 6, and the magnesium-alumina ratio was 10. The mixture was reacted at 300°C for 2 hours, and solid-liquid separation was performed. The solid phase was washed to obtain a mixture of magnesium aluminum hydrotalcite and silicates.

[0058] Example 2 Microclinic potassium feldspar ore was used as raw material, containing potassium feldspar, sodium feldspar, quartz, and trace amounts of arsenic and cadmium impurities, with a K₂O wt.% of approximately 8%. The ore was pulverized to 400 mesh and ball-milled with magnesium hydroxide powder (containing 10% molar fraction of lithium hydroxide). The MgO / SiO₂ molar ratio in the powder mixture was 6. The mixture was calcined at 1100℃ for 1.5 hours. After calcination, the mixture was cooled to 200℃ and mixed with a 9 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 60℃ and leached with stirring for 1 hour, ending with a sulfuric acid concentration of approximately 0.05 mol / L. Solid-liquid separation yielded an amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contains magnesium, potassium, sodium, and trace aluminum ions. The pH of the solution is neutralized to approximately 7.5 with magnesium oxide. Polyaluminum chloride is added to remove trace aluminum ions. Solid-liquid separation is performed, and the aluminum salt precipitate is washed and reserved. The washing liquid is returned to the acid leaching section. The dealuminated solution is evaporated, concentrated, and crystallized at -10℃ to precipitate sodium sulfate. Evaporation continues after heating, and crystallization continues at 15℃. Solid-liquid separation yields hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer product) and a mixed solution of magnesium sulfate and sodium sulfate. The solution after potassium fertilizer precipitation, aluminosilicate gel, and dealuminated precipitate are mixed, and magnesium hydroxide is added to adjust the pH to 8. The silicon-to-aluminum ratio is 12, and the magnesium-to-aluminum ratio is 4. The reaction is carried out at 200℃ for 3 hours, followed by solid-liquid separation. The solid phase is washed to obtain lithium-containing magnesium soapstone. The arsenic and cadmium content in the liquid phase is both below 5 μg / L. The liquid phase is directly returned to the magnesium soapstone synthesis batching section.

[0059] Example 3 Containing minerals such as potassium feldspar and chlorite, along with trace amounts of iron, lead, and strontium compounds, the mixture was pulverized to 300 mesh and extruded and mixed with magnesium carbonate powder (containing 50% zinc oxide powder). The MgO / SiO2 molar ratio in the powder mixture was 8. The mixture was calcined at 1300℃ for 1 hour, then cooled to 260℃ and mixed with a 2 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 50℃ and leached with stirring for 10 hours, ending with a sulfuric acid concentration of approximately 0.01 mol / L. Solid-liquid separation yielded an amorphous aluminosilicate gel solid and a sulfate solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contains magnesium, potassium, sodium, zinc, and trace aluminum ions. The pH of the solution is neutralized to approximately 7.0 with magnesium oxide. Polyaluminum chloride is added to remove trace aluminum ions. Solid-liquid separation is performed, and the aluminum salt precipitate is washed and reserved. The washing liquid is returned to the acid leaching section. The dealuminized solution is evaporated, concentrated, and crystallized at 35°C. Solid-liquid separation is then performed to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer product) and a mixed solution of magnesium sulfate, sodium sulfate, and zinc sulfate. The solution after potassium fertilizer precipitation, aluminosilicate gel, and dealuminized precipitate are mixed, and magnesium hydroxide is added to adjust the pH to 11. The silicon-to-aluminum ratio is 16, and the magnesium-to-aluminum ratio is 6. The reaction is carried out at 80°C for 12 days. Solid-liquid separation is performed, and the solid phase is washed to obtain zinc-magnesium soapstone. The iron and lead content in the liquid phase is less than 1 μg / L, and the strontium content is less than 5 μg / L. The liquid phase is returned to the magnesium soapstone synthesis batching section.

[0060] Example 4 Mineral raw materials containing potassium feldspar and spodumene were pulverized to 50 mesh and mixed with magnesite powder (containing 10% sodium carbonate). The MgO / SiO2 molar ratio in the powder mixture was 5. The mixture was calcined at 850℃ for 5 hours. After calcination, the mixture was cooled to 280℃ and mixed with a 4 mol / L sulfuric acid aqueous solution. The resulting solid-liquid system was kept at 100℃ and leached with stirring for 3 hours, ending with a sulfuric acid concentration of approximately 0.04 mol / L. Solid-liquid separation yielded an amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid was washed with pure water, and the acidic washing liquid was recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contained magnesium, potassium, sodium, lithium, and trace aluminum ions. The pH of the solution was neutralized to approximately 6.5 with magnesium oxide, and polyaluminum chloride was added to remove trace aluminum ions. Solid-liquid separation was then performed, and the aluminum salt precipitate was washed and reused. The washing liquid was returned to the acid leaching section. After dealuminization, the solution is evaporated, concentrated, crystallized at 25°C, and then separated into solid and liquid phases to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer product) and a mixed solution of magnesium sulfate, sodium sulfate, and zinc sulfate. The solution after potassium fertilizer precipitation, aluminosilicate gel, and dealuminization precipitate are mixed, magnesium hydroxide is added, the pH is adjusted to 9, the silicon-to-aluminum ratio is 10, and the magnesium-to-aluminum ratio is 8. The mixture is reacted at 160°C for 1 day, and then separated into solid and liquid phases. The solid phase is washed to obtain lithium-containing magnesium soapstone, and the liquid phase is returned to the magnesium soapstone synthesis batching section.

[0061] Example 5 Mineral raw materials containing potassium feldspar, quartz, etc., are pulverized to 150 mesh and ball-milled with basic magnesium carbonate powder. The MgO / SiO2 molar ratio in the powder mixture is 7. The mixture is calcined at 950℃ for 3 hours. After calcination, the mixture is cooled to 200℃ and mixed with a 7mol / L sulfuric acid aqueous solution. The resulting solid-liquid system temperature is 70℃. The mixture is then held at this temperature and stirred for 4 hours, with a final sulfuric acid concentration of approximately 0.02 mol / L. Solid-liquid separation yields amorphous aluminosilicate gel solid and a sulfate mixed solution. The aluminosilicate solid is washed with pure water, and the acidic washing liquid is recovered and used to prepare the sulfuric acid leaching solution for the calcined mixture. The sulfate mixed solution contains magnesium, potassium, sodium, lithium, and trace aluminum ions. The pH of the solution is neutralized to approximately 7.2 with magnesium oxide. Polyaluminum chloride is added to remove trace aluminum ions from the solution. Solid-liquid separation is then performed, and the aluminum salt precipitate is washed and reused. The washing liquid is returned to the acid leaching section. After dealuminization, the solution is evaporated, concentrated, crystallized at 25°C, and then separated into solid and liquid phases to obtain hydrated potassium magnesium sulfate (washed and dehydrated to obtain potassium magnesium sulfate fertilizer product) and magnesium sulfate solution. The solution after potassium fertilizer precipitation, aluminosilicate gel, and dealuminization precipitate are mixed, magnesium hydroxide is added, the pH is adjusted to 9.5, the silicon-to-aluminum ratio is 24, the magnesium-to-aluminum ratio is 9, and the reaction is carried out at 220°C for 8 hours. After solid-liquid separation, the solid phase is washed to obtain magnesium soapstone, and the liquid phase is returned to the magnesium soapstone synthesis batching section.

[0062] In addition, the applicant also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0063] It should be understood that the technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made to the technical solutions of the present invention without departing from the spirit and scope of the claims are within the scope of protection of the present invention.

Claims

1. A method for producing potassium salts and co-producing magnesium saponite using a calcination-hydrothermal composite process, characterized in that, include: Potassium-containing feldspar minerals are crushed, then mixed with calcination aids and subjected to calcination, acid leaching, and solid-liquid separation to obtain aluminosilicate gel solid and sulfate mixed solution; wherein, the calcination aids include magnesium compounds or a mixture of magnesium compounds and magnesium substitutes. The sulfate mixture solution was neutralized, dealuminized, evaporated, concentrated and crystallized to obtain hydrated potassium magnesium sulfate, aluminum salt precipitate and crystallization tail liquid; Furthermore, the aluminum salt precipitate, crystallization tail liquid, and aluminosilicate gel solid are mixed and the pH value is adjusted to 8-11, followed by a hydrothermal reaction to obtain magnesium soapstone.

2. The method according to claim 1, characterized in that: The potassium feldspar in the potassium-containing minerals includes any one or more combinations of microcline, orthoclase, sorbite, and sanidine. And / or, the potassium-containing feldspar minerals are crushed to a particle size of 50-400 mesh, and the obtained crushed product is mixed with calcination aids by stirring, mechanical ball milling or extrusion mixing.

3. The method according to claim 1, characterized in that: The magnesium compounds include any one or more combinations of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, hydrated magnesium silicate, hydrated magnesium carbonate, basic magnesium carbonate, magnesite, hydromagnesite, and hydrocrystalline magnesite. And / or, the magnesium substitute compound includes any one or more combinations of sodium compounds, lithium compounds, and zinc compounds; preferably, the magnesium substitute compound includes any one or more combinations of oxides, carbonates, hydroxides, and silicates of sodium, lithium, or zinc.

4. The method according to claim 1, characterized in that: The molar ratio of the metal element in the magnesium substitute compound to the magnesium element in the magnesium compound in the mixture formed by the magnesium compound is ≤1. And / or, in the potassium-containing feldspar minerals and roasting aids used, the molar ratio of MgO / SiO2 is 4 to 8, calculated as MgO / SiO2.

5. The method according to claim 1, characterized in that, include: The potassium-containing feldspar minerals are crushed, mixed with a roasting aid, and calcined at 850-1300℃ for 1-5 hours. The mixture is then cooled to 200-300℃, and the resulting product is mixed with sulfuric acid solution to form a solid-liquid system at 50-100℃. The mixture is then fully leached, and finally separated into solid and liquid components to obtain aluminosilicate gel solid and sulfate mixed solution.

6. The method according to claim 5, characterized in that: The concentration of the sulfuric acid solution is 2~9 mol / L, and after complete leaching, the concentration of the sulfuric acid solution in the solid-liquid system is 0.01~0.05 mol / L; And / or, the leaching time is 1 to 10 hours; And / or, the cations in the sulfate mixed solution include magnesium ions, potassium ions, sodium ions, and aluminum ions.

7. The method according to claim 1, characterized in that, include: Magnesium oxide and / or magnesium hydroxide are added to the sulfate mixture for neutralization treatment, and the pH value is adjusted to 6.0~7.5; And / or, the dealuminization is performed by adding polyaluminum chloride to the product obtained from neutralization; And / or, the crystallization temperature is -10℃ to 35℃; And / or, the products obtained after crystallization include hydrated magnesium sulfate, magnesium sulfate heptahydrate, sodium sulfate and anhydrous sodium sulfate; And / or, the crystallization tail liquid after crystallization includes a magnesium sulfate solution; And / or, the method further includes: the hydrated potassium magnesium sulfate is washed and dehydrated to obtain potassium magnesium sulfate fertilizer.

8. The method according to claim 1, characterized in that: In the aluminum salt precipitate, crystallization tail liquid, and aluminosilicate gel solid used, the molar ratio of SiO2 / Al2O3 is 6~24 and the molar ratio of MgO / Al2O3 is 4~10, based on SiO2 / Al2O3 and MgO / Al2O3.

9. The method according to claim 1, characterized in that: The aluminum salt precipitate, crystallization tail liquid, and aluminosilicate gel solid are mixed and the pH value is adjusted using a pH adjusting agent, wherein the pH adjusting agent includes any one or more combinations of magnesium hydroxide, magnesium oxide, sodium carbonate, and sodium hydroxide.

10. The method according to claim 1, characterized in that: The hydrothermal reaction is carried out at a temperature of 80~300℃ for a duration of 2 hours to 12 days.